PENERAPAN METODE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR PEMELIHARAAN MESIN KENDARAAN RINGAN SISWA KELAS XI TKR SMKN 1 MANDAU TAHUN PELAJARAN 2018/2019 - Riki Fitrianto (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
The purpose of this study is to find out the results of learning the training of Light Vehicle Machine Maintenance through the application of Jigsaw learning model. The learning outcomes of Light Vehicle Engine Maintenance training are expected to increase, so that the Basic Competencies to be achieved in the learning process can be mastered by students to the maximum. This research was conducted at SMKN 1 Mandau, Mandau Clean Water Pipe road. The subjects in this study were students kls XI TKR Year 2018/2019 which amounted to 25 students who were all male. The research method uses a class action research method. Many actions as much as twice in two cycles. Each tap cycle consists of four stages including action planning, implementation of the indakan, observation of the results of actions, and reflection of the results of actions. The results showed that this post-act condition averaged the average score obtained by Cycle I = 72.0 (42.3%), and the average score in Cycle II = 85.33 (88%), then from pre-act conditions compared to cycle II has increased. This indicates that the use of jigsaw learning models can improve the learning outcomes of Light Vehicle Machine Maintenance courses. Based on the conclusion of this study needs to be tested in other subjects.